KEAKUAN INDIVIDU SEBAGAI INSAN TAQWIM (Potret Kajian Filsafat) - Taufiqurrahman Taufiqurrahman (Universitas Islam Negeri Imam Bonjol Padang, 2018)
God’s statement in Surah al-Tin, verse 4 is a suggestion for mankind to make an introduction to itself. It's like a person's behavior makes a circle with anchors. When the circle is very small, one must be extra careful to set the center point to keep the circle full. Truly the perfect message of the Qur'an in Surah al-Kahf, verse 19, which is precisely the point of the whole verse; which calls on humans to be walyatalaththaf, ie extra caution, full of lathifeness, self-sensitivity. Therefore, the caution in passing through this life is often likened to passing through a haircut split seven. What is that meaning? The sharpest self-sensitivity, so that human beings become like super filaments.